2020
DOI: 10.1186/s13223-020-00454-w
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to biologics in a patient with severe asthma and ABPA: a role for dupilumab?

Abstract: Background Allergic bronchopulmonary aspergillosis (ABPA) is a severe hypersensitivity reaction to aspergillus species colonizing the airways of patients with asthma or cystic fibrosis. Biologics including anti-IgE and anti-IL5 antibodies have strongly changed the treatment of severe asthmatics and have partly been reported to be effective in the treatment of ABPA. Recently, dupilumab, an anti-IL4-Rα antibody which inhibits signaling by the Th2-cytokines IL4 and IL13, has been approved for the treatment of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 13 publications
1
30
0
1
Order By: Relevance
“…The administration of dupilumab decreases the peripheral blood count of eosinophils and the serum levels of IgE in patients with severe bronchial asthma[ 9 ]. Several reports have also demonstrated the efficacy of dupilumab in ABPA (Table 1 )[ 5 , 9 - 11 ]. For example, Mümmler et al [ 5 ] reported a case of bronchial asthma associated with ABPA in which the administration of omalizumab or dupilumab reduced the dose of oral glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The administration of dupilumab decreases the peripheral blood count of eosinophils and the serum levels of IgE in patients with severe bronchial asthma[ 9 ]. Several reports have also demonstrated the efficacy of dupilumab in ABPA (Table 1 )[ 5 , 9 - 11 ]. For example, Mümmler et al [ 5 ] reported a case of bronchial asthma associated with ABPA in which the administration of omalizumab or dupilumab reduced the dose of oral glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have also demonstrated the efficacy of dupilumab in ABPA (Table 1 )[ 5 , 9 - 11 ]. For example, Mümmler et al [ 5 ] reported a case of bronchial asthma associated with ABPA in which the administration of omalizumab or dupilumab reduced the dose of oral glucocorticoids. Also, Mikura et al [ 9 ] and Ramonell et al [ 10 ] reported cases of ABPA in which the administration of dupilumab, but not that of mepolizumab, made possible a reduction in the dose of oral glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of serum IgE was over 6000 IU/mL (out of range) in this case, calling for doses above the nomogram-based upper limit. Indeed, some case reports describe an insufficient efficacy of omalizumab for ABPM [ 13 ]. We thus doubted the efficacy of omalizumab in this case and decided not to use it.…”
Section: Discussionmentioning
confidence: 99%
“…Dupilumab, a humanized monoclonal antibody against IL-4 receptor, also has potential for treatment of ABPM [ 13 , 22 ]. We had no idea whether mepolizumab or dupilumab was preferable for this case from the perspective of biological effects.…”
Section: Discussionmentioning
confidence: 99%